2023
DOI: 10.1155/2023/8427200
|View full text |Cite
|
Sign up to set email alerts
|

Secretome of Mesenchymal Stromal Cells as a Possible Innovative Therapeutic Tool in Facial Nerve Injury Treatment

Abstract: Facial nerve palsy is a serious neurological condition that strongly affects patient everyday life. Standard treatments provide insufficient improvement and are burdened with the risk of severe complications, e.g., facial synkinesis. Mesenchymal stromal cell-based therapies are a novel and extensively developed field which offers new treatment approaches with promising results in regards to the nervous tissue regeneration. The potential of mesenchymal stromal cells (MSCs) to aid the regeneration of damaged ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…However, increasing evidence has suggested that the survival rate and efficiency of MSCs in differentiating into target cells after transplantation are generally too low to match the observed beneficial reparative effects. [ 14 ] Recent and compelling evidence now suggests that stem cells exert their effects indirectly through the paracrine release of cell‐active factors (e.g., growth factors) [ 15 ] and vesicles (e.g., exosomes) [ 16 ] in tissue repair. [ 17 ] The advancement of “cell‐free therapies” derived from stem cells has emerged as a promising approach, providing reparative effects comparable to stem cell therapies.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing evidence has suggested that the survival rate and efficiency of MSCs in differentiating into target cells after transplantation are generally too low to match the observed beneficial reparative effects. [ 14 ] Recent and compelling evidence now suggests that stem cells exert their effects indirectly through the paracrine release of cell‐active factors (e.g., growth factors) [ 15 ] and vesicles (e.g., exosomes) [ 16 ] in tissue repair. [ 17 ] The advancement of “cell‐free therapies” derived from stem cells has emerged as a promising approach, providing reparative effects comparable to stem cell therapies.…”
Section: Introductionmentioning
confidence: 99%